Tectonics in Architecture of Tanean Lanjhang and Osing House: The Impact on the Growth of Space Area - Catherine Kirsten Eka Wijaya; Agus Dwi Hariyanto; Phylicia Deosephine Soegiono; Eveelyn Febe Gunawan (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
This research was initiated by an interest in vernacular architecture, which adapts to fit the changing demands of its inhabitants. Cultural variations and differing population demands can cause spatial planning patterns to vary even within a province or between nearby places. Tectonic formations are produced by the growth of vernacular houses. In addition to understanding the distinctive tectonic structures through the connections of elements in the expanded spaces, this study attempts to identify and classify the spatial arrangement patterns in the vernacular houses of Tanean Lanjhang and Osing. Tanean Lanjhang and Osing buildings are examples of vernacular architecture known as